Chicago Lawyers Survey, 1975 - Heinz, John P. ([Verlag nicht ermittelbar], 1985)
This data collection contains information gathered in 1975 on attorneys in Chicago, Illinois. The purpose of this data collection was to describe and analyze the social organization of the legal profession in Chicago. Several major aspects of the legal profession were investigated: the organization of lawyers' work, the social stratification within the Chicago Bar Association, prestige within the profession, lawyers' personal values, career patterns and mobility, networks of association, and the "elites" within the profession. Specific questions elicited information on areas of law in which the respondents spent most of their time practicing, and the ethnicities, educational background, religion, political affiliation, bar association memberships, and sex of respondents' friends and colleagues. Other variables probe respondents' backgrounds, such as father's occupation, home town, law school from which the respondent graduated, religious and political affiliations, ethnicity, sex, and income.